PENYULUHAN PENYELESAIAN SENGKETA PERADILAN TATA USAHA NEGARA - Sutanto, Very Werson; Yori, Aurelius Kasimirus; Lumme, Andreas; Padang, Paulus T.T. (Nindikayla Institute, 2023)
This legal counselling carried out at Village Official Hall of Kamali Pentalluan, District of Makale, Regency of Tana Toraja. In general sense, the lack of legal knowledge surrounding administrative dispute settlement on behalf of Administrative Court still remains up to now and finally the needs of legal solution laid down on reverie. Based on this situation, village inhabitants were hard to overcome and to settle the administrative legal case themselves. In turn to accompany settling these needs, legal counselling of administrative dispute settlement carried out. The counselling held on flow of administrative dispute settlement. Through this counselling, all inhabitants realizes that well-understanding of administrative dispute settlement basically essential and legal knowledge surrounding the idea significantly increased